Pelestarian dan Perawatan Koleksi di Perpustakaan Umum - Cita, Lisa Engla Kade; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
The purpose of this study were: (1) describe the factors causing damage to the collection in Solok City Public Library, (2) describe what actions need to be done on the collections that have been damaged in Solok City Public Library. Types of research conducted included into qualitative research. The data was collected through observation and interviews. Based on the results of direct observation and interviews with library staff can be concluded, first, the cause of damage to library materials in the city's public library Solok are: (1) factors biota, the book caused damage by insects, termites, nerds, (2) physical factors, the effect of temperature and humidity, the effect of unfavorable light, and air pollution. Second, the techniques of conservation and maintenance of library materials is less applicable in Solok City Public Library. Keywords: preservation; collections; public